2017
DOI: 10.1080/09540105.2017.1376038
|View full text |Cite
|
Sign up to set email alerts
|

Hapten synthesis and production of specific antibody against 3-amino-5-morpholinomethyl-2-oxazolidone for immunoassay without derivatisation

Abstract: 2018) Hapten synthesis and production of specific antibody against 3-amino-5-morpholinomethyl-2-oxazolidone for immunoassay without derivatisation, Food and Agricultural Immunology, 29:1, 332-345, ABSTRACT Immunoassay direct for 3-amino-5-morpholinomethyl-2-oxazolidone (AMOZ), the metabolite of furaltadone, based on a specific antibody was usually unavailable due to its small molecule weight. In this work, a hapten with a double bond and an active carboxyl group was designed and then conjugated to peptide dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It was reported that more similar the characteristics of a hapten derivative are to the target, such as size, shape (geometry) and electronic properties, the more likely specific antibodies will be produced [38,39]. Moreover, it is also suggested that a short semi-rigid unsaturated double bond structure is generally good for the production of desired antibodies [40][41][42]. Based on these ideas, haptens with short spacer arms or unsaturated double bond arms were designed and the similarity between drugs and haptens was analyzed by molecular simulation.…”
Section: Design and Screening Of The Haptensmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that more similar the characteristics of a hapten derivative are to the target, such as size, shape (geometry) and electronic properties, the more likely specific antibodies will be produced [38,39]. Moreover, it is also suggested that a short semi-rigid unsaturated double bond structure is generally good for the production of desired antibodies [40][41][42]. Based on these ideas, haptens with short spacer arms or unsaturated double bond arms were designed and the similarity between drugs and haptens was analyzed by molecular simulation.…”
Section: Design and Screening Of The Haptensmentioning
confidence: 99%
“…In summary, it was an efficient strategy for target-derived hapten to be designed rationally through structure simulation, and further confirmed that the well-mimicked hapten TYL-CHO had stable immunogenicity to induce an antibody against tylosin in mice (Table 1). suggested that a short semi-rigid unsaturated double bond structure is generally good for the production of desired antibodies [40][41][42]. Based on these ideas, haptens with short spacer arms or unsaturated double bond arms were designed and the similarity between drugs and haptens was analyzed by molecular simulation.…”
Section: Design and Screening Of The Haptensmentioning
confidence: 99%
“…However, how could haptens be designed to produce antibodies with an excellent and desired analytical performance such as broad group specificity, high sensitivity, and good affinity? Our past and ongoing research about hapten design for achieving a desired antibody had also yielded some useful results and discoveries such as unsaturated arm strategy (Huang et al, 2019;Liu et al, 2017;Luo et al, 2019;Shen et al, 2007;Yang et al, 2013), molecular orbital energy theory (Xu et al, 2010), electrostatic potential (ESP) and lipophilicity (LP) factors (He et al, 2021;Huang et al, 2019), etc. All the above strategies could increase hapten-specific immune efficacy to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Furaltadone (Figure S1), a kind of nitrofuran antibiotic, was once widely used in the livestock, poultry and aquaculture industries due to its dominant antibacterial activity. Howerve, it has been banned for using in edible animals in many countries attributing to furaltadone and its metabolites are all highly toxic, teratogenic, carcinogenic and mutagenic (Guo et al, 2017;Li et al, 2017;Liu et al, 2018). It is disappointed that application of furaltadone illegal is still very serious in many countries, including China, because of its good efficacy and low price.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with instrumental methods such as high-performance liquid chromatography (HPLC) and liquid chromatography-tandem mass spectrometry (LC-MS/MS), immunoassays possess the advantages of being simple, fast, sensitive and low cost (Van Emon, 2010;Wang et al, 2016a). As a high-throughput screening method, immunoassays have already been explored and employed in the field of rapid determination of AMOZ residue in edible animal tissues (Dai et al, 2015;Deng et al, 2016;Jester et al, 2014;Li et al, 2014;Liu et al, 2018;Shen et al, 2012;Xie et al 2019;Xu et al, 2013aXu et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%